Giai PT
\(2x^2+\sqrt{1-x}+2x\sqrt{1-x^2}-1=0\)
Giai PT 2x+1 +x\(\sqrt{x^2+2}\)+(x+1)\(\sqrt{x^2+2x+3}\)= 0
Copy trên mạng nè:
Try the following:Use different phrasing or notationsEnter whole words instead of abbreviationsAvoid mixing mathemaal and other notationsCheck your spellingGive your input in EnglishOther tips for using Wolfram|Alpha:Wolfram|Alpha answers specific questions rather than explaining general topicsEnter "2 cups of sugar", not "nutrition information"You can only get answers about objective factsTry "highest mountain", not "most beautiful painting"Only what is known is known to Wolfram|AlphaAsk "how many men in Mauritania", not "how many monsters in Loch Ness"Only public information is availableRequest "GDP of France", not "home phone of Michael Jordan"Examples by Topic Quick video overviewInput: Result: Plot: Alternate forms: Complex solutions:Approximate formsStep-by-step solution Roots in the complex plane:giai pt
a) \(\sqrt{1+\sqrt{1-x^2}.}[\sqrt{\left(1-x\right)^3}-\sqrt{\left(1+x\right)^3}]=2+\sqrt{1-x^2}\)
b) \(\sqrt{1-x}-2x\sqrt{1-x^2}-2x^2+1=0\)
c) \(64x^6-112x^4+56x^2-7=2\sqrt{1-x^2}\)
a/ ĐKXĐ: ...
Đặt \(\left\{{}\begin{matrix}\sqrt{1-x}=a\ge0\\\sqrt{1+x}=b\ge0\end{matrix}\right.\) được hệ:
\(\left\{{}\begin{matrix}\sqrt{1+ab}\left(a^3-b^3\right)=2+ab\\a^2+b^2=2\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}\sqrt{1+ab}\left(a-b\right)\left(a^2+ab+b^2\right)=a^2+b^2+ab\\a^2+b^2=2\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}\sqrt{1+ab}\left(a-b\right)=1\\a^2+b^2=2\end{matrix}\right.\) \(\left(a\ge b\right)\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left(1+ab\right)\left(a-b\right)^2=1\\a^2+b^2=2\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left(1+ab\right)\left(2-2ab\right)=1\\a^2+b^2=2\end{matrix}\right.\)
\(\Rightarrow\left\{{}\begin{matrix}1-a^2b^2=\frac{1}{2}\\a^2+b^2=2\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}a^2b^2=\frac{1}{2}\\a^2+b^2=2\end{matrix}\right.\)
Theo Viet đảo, \(a^2;b^2\) là nghiệm của:
\(t^2-2t+\frac{1}{2}=0\Rightarrow\left[{}\begin{matrix}t=\frac{2+\sqrt{2}}{2}\\t=\frac{2-\sqrt{2}}{2}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}1-x=\frac{2+\sqrt{2}}{2}\\1-x=\frac{2-\sqrt{2}}{2}\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=-\frac{\sqrt{2}}{2}\\x=\frac{\sqrt{2}}{2}\end{matrix}\right.\)
2 phần còn lại ko biết giải theo kiểu lớp 10, chỉ biết lượng giác hóa, bạn tham khảo thôi :(
b/ Đặt \(x=cos2t\) pt trở thành:
\(\sqrt{1-cos2t}-2cos2t.\sqrt{1-cos^22t}-\left(2cos^22t-1\right)=0\)
\(\Leftrightarrow\sqrt{2}sint-2sin2t.cos2t-cos4t=0\)
\(\Leftrightarrow\sqrt{2}sint-sin4t-cos4t=0\)
\(\Leftrightarrow\sqrt{2}sint=sin4t+cos4t=\sqrt{2}sin\left(4t+\frac{\pi}{4}\right)\)
\(\Leftrightarrow sin\left(4t+\frac{\pi}{4}\right)=sint\)
\(\Leftrightarrow\left[{}\begin{matrix}4t+\frac{\pi}{4}=t+k2\pi\\4t+\frac{\pi}{4}=\pi-t+k2\pi\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}t=-\frac{\pi}{12}+\frac{k2\pi}{3}\\t=-\frac{\pi}{20}+\frac{k2\pi}{5}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=cos\left(-\frac{\pi}{6}+\frac{k4\pi}{3}\right)\\x=cos\left(-\frac{\pi}{10}+\frac{k4\pi}{5}\right)\end{matrix}\right.\) với \(k\in Z\)
c/ Đặt \(x=cost\)
\(64cos^6t-112cos^4t+56cos^2t-7=2\sqrt{1-cos^2t}\)
\(\Leftrightarrow64cos^6t-112cos^4t+56cos^2t-7=2sint\)
Nhận thấy \(cost=0\) không phải nghiệm, pt tương đương:
\(64cos^7t-112cos^5t+56cos^3t-7cost=2sint.cost\)
\(\Leftrightarrow cos7t=sin2t=cos\left(\frac{\pi}{2}-2t\right)\)
\(\Leftrightarrow\left[{}\begin{matrix}7t=\frac{\pi}{2}-2t+k2\pi\\7t=2t-\frac{\pi}{2}+k2\pi\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}t=\frac{\pi}{18}+\frac{k2\pi}{9}\\t=-\frac{\pi}{10}+\frac{k2\pi}{5}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=cos\left(\frac{\pi}{18}+\frac{k2\pi}{9}\right)\\x=\left(-\frac{\pi}{10}+\frac{k2\pi}{5}\right)\end{matrix}\right.\)
Ý tưởng của người ra đề khá kì quặc, công thức \(cos7a\) kia thực sự là chứng minh rất mất thời gian
Giai pt
\(\sqrt{2x+1}-2\sqrt{2-x}=3\sqrt[4]{\left(1-2x\right)\left(x-2\right)}\)
GIẢI CÁC PT SAU:
\(\sqrt{x^2+5x+1}=\sqrt{x+1}\)
\(\sqrt{x^2+2x+4}=\sqrt{2-x}\)
\(\sqrt{2x+4}-\sqrt{2-x}=0\)
Lời giải:
1. ĐKXĐ: $x\geq \frac{-5+\sqrt{21}}{2}$
PT $\Leftrightarrow x^2+5x+1=x+1$
$\Leftrightarrow x^2+4x=0$
$\Leftrightarrow x(x+4)=0$
$\Rightarrow x=0$ hoặc $x=-4$
Kết hợp đkxđ suy ra $x=0$
2. ĐKXĐ: $x\leq 2$
PT $\Leftrightarrow x^2+2x+4=2-x$
$\Leftrightarrow x^2+3x+2=0$
$\Leftrightarrow (x+1)(x+2)=0$
$\Leftrightarrow x+1=0$ hoặc $x+2=0$
$\Leftrightarrow x=-1$ hoặc $x=-2$
3.
ĐKXĐ: $-2\leq x\leq 2$
PT $\Leftrightarrow \sqrt{2x+4}=\sqrt{2-x}$
$\Leftrightarrow 2x+4=2-x$
$\Leftrightarrow 3x=-2$
$\Leftrightarrow x=\frac{-2}{3}$ (tm)
\(2\sqrt{x}+\dfrac{1}{\sqrt{x}}=2x+\dfrac{1}{2x}+\dfrac{1}{2}\)
giai pt vo ti
giai pt
\(\sqrt{x+3}-\sqrt{x-1}=\sqrt{2x+2}\)
\(\sqrt{x^2-x+4}-x^2+x+2=0\)
\(\sqrt[3]{x+7}+\sqrt[3]{1-x}=2\)
a) \(\sqrt{x+3}-\sqrt{x-1}=\sqrt{2x+2}\)
Điều kiện: \(\hept{\begin{cases}x+3\ge0\\x-1\ge0\\2x+2\ge0\end{cases}}\Leftrightarrow\hept{\begin{cases}x\ge-3\\x\ge1\\x\ge-1\end{cases}\Leftrightarrow x\ge1}\)
\(\Leftrightarrow\left(\sqrt{x+3}-\sqrt{x-1}\right)^2=\left(\sqrt{2x+2}\right)^2\)
\(\Leftrightarrow x+3-2\sqrt{\left(x+3\right)\left(x-1\right)}+x-1=2x+2\)
\(\Leftrightarrow2x+2-2\sqrt{\left(x+3\right)\left(x-1\right)}=2x+2\)
\(\Leftrightarrow-2\sqrt{\left(x+3\right)\left(x-1\right)}=0\)
\(\Leftrightarrow\left(x+3\right)\left(x-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x+3=0\\x-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=-3\left(l\right)\\x=1\left(n\right)\end{cases}}\)
Vậy \(S=\left\{1\right\}\)
giai cac phuong trinh
a)\(2x^4+5x^3+x^2+5x+2=0\)
b)\(\sqrt{x-1}-\sqrt[3]{2-x}=1\)
c)\(x-\sqrt{x}+1=\sqrt{2x^2-30x+2}\)
d)\(2x^2+3x+7=\left(x-5\right)\sqrt{2x^2+1}\)
e)\(\sqrt{x-2}+\sqrt{4-x}=2x^2-5x-1\)
giải các PT sau :
a) \(\left|2x+3\right|-\left|x\right|+\left|x-1\right|=2x+4\)
b) \(\sqrt{x}-\dfrac{4}{\sqrt{x+2}}+\sqrt{x+2}=0\)
c) \(\sqrt{x+\sqrt{2x-1}}+\sqrt{x-\sqrt{2x-1}}=\sqrt{2}\)
d) \(x+\sqrt{x+\dfrac{1}{2}+\sqrt{x+\dfrac{1}{4}}}=4\)
e) \(\sqrt{4x+3}+\sqrt{2x+1}=6x+\sqrt{8x^2+10x+3}-16\)
f)\(\sqrt[3]{x-2}+\sqrt{x+1}=3\)
GIÚP MÌNH VỚI MÌNH ĐANG CẦN GẤP
giai pt :\(2x^3-x^2+\sqrt{2x^3-3x+1}=3x+1+\sqrt[3]{x^2+2}\)
x= 0.761322463768116,
x= 0.369494467346496,
x=1.57660410301179